1999
DOI: 10.1021/la981608c
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Colloidal Particles from Quartz Collector Surfaces As Stimulated by the Passage of Liquid−Air Interfaces

Abstract: Micron-sized particles adhering to collector surfaces can be detached by passing a liquid−air interface over the adhering particles. Theoretically, the efficiency of particle detachment depends on the interface velocity, the liquid surface tension, the viscosity, and the particle−substratum interaction forces. In this study we perfuse an air bubble through a parallel-plate flow chamber to study detachment of polystyrene particles from a quartz collector surface, at different interface velocities and liquid sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 32 publications
5
67
2
Order By: Relevance
“…They found that colloid detachment from the solid surface was more at lower interface velocity. A similar observation has been made for particle detachment by air-bubble moving at higher speed (> 8cmh −1 ) [30,31].…”
Section: Attachment At the Liquid-gas Interfacessupporting
confidence: 82%
See 1 more Smart Citation
“…They found that colloid detachment from the solid surface was more at lower interface velocity. A similar observation has been made for particle detachment by air-bubble moving at higher speed (> 8cmh −1 ) [30,31].…”
Section: Attachment At the Liquid-gas Interfacessupporting
confidence: 82%
“…These are interception of the particle, attachment or thinning of the liquid film in between the particle and the liquid-gas interface, and stabilization of the particle on the liquid-gas interface [22,30,67,70]. The total detachment probability (P det ) is defined as [22]:…”
Section: Attachment At the Liquid-gas Interfacesmentioning
confidence: 99%
“…The probability of collision of microbubbles with bacterial cells or entities depends on the cross-sectional area exposed to the flow and is evidently larger for adhering coaggregates than for single bacteria. In the studies by Gómez-Suárez et al (7)(8)(9), the collision efficiency was invariably 1, because air-liquid interfaces fully spanning the width of their parallel plate flow chamber were used. For microbubbles the situation is different, however.…”
Section: Discussionmentioning
confidence: 99%
“…1). A detailed analysis of the surface tension forces causing this detachment was first given in the field of semiconductors (12,13), and later the method was successfully used to detach colloidal particles (7,15) and bacteria (8) from surfaces in a parallel plate flow chamber. Surface tension detachment forces range from 10 Ϫ9 to 10 Ϫ7 N, depending on the surfaces involved, and are several orders of magnitude larger than gravitational, buoyancy, and hydrodynamic forces acting on microorganisms (15).…”
mentioning
confidence: 99%
“…These processes have only recently been fully understood and need to be introduced into microbiology in order to stimulate methodological advances in the field. Detachment of adhering polystyrene particles by the passage of air bubbles has been demonstrated to be more efficient when (i) the velocity of the passing air bubble decreases (19,20), (ii) the air-liquid interfacial tension increases (19,20), (iii) particle size decreases (17), (iv) the substratum surface is more hydrophobic (19), and (v) the substratum surface is negatively charged (18).…”
mentioning
confidence: 99%